Subarachnoid Hemorrhage (SAH) - Wulandari, Dwi Astuti; Hunaifi, Ilsa; Sampe, Ester (Faculty of Medicine Universitas Mataram, 2021)
Approximately, 10-20% of stroke cases in a year caused by a hemorrhagic strokes. The most dangerous and deadly of hemorrhagic stroke’s is subarachnoid hemorrhage (SAH). SAH have higher impact on economic, morbidity, and mortality than other types of stroke even though the prevalence is quite low. About 80% of non-trauma subarachnoid hemorrhage (SAH) cases are caused by rupture of intracranial aneurysm, which encourages blood to fill the subarachnoid space and stimulates the surrounding structures, it’s cause pathognomonic symptoms of stiff neck and thunderclap headache. Even though there are typical symptoms, misdiagnose of this stroke is still happens. Therefore, a comprehension of all aspects that are related to subarachnoid hemorrhage is very important in optimizing patient ability and service. Keywords: stroke, subarachnoid hemorrhage, intracranial aneurysms